Efficacy and airway complications of Parker Flex-Tip tubes and standard endotracheal tubes during airway manipulation: A meta-analysis and trial sequential analysis. Issue 8 (August 2021) - Hung, Kuo-Chuan; Chen, Jen-Yin; Feng, I-Jung; Chiang, Min-Hsien; Wu, Shao-Chun; Chen, I-Wen; Lin, Yao-Tsung; Chang, Ying-Jen; Wu, Zhi-Fu; Lu, Hsiao-Feng; Sun, Cheuk-Kwan
Abstract : BACKGROUND: Despite reported superior intubation outcomes associated with Parker Flex-Tip (PFT) tubes compared with those associated with standard polyvinylchloride tubes, the efficacy and safety of PFT tubes remain uncertain. OBJECTIVES: To compare the intubation outcomes between PFT and conventional standard polyvinylchloride tubes. DESIGN: Meta-analysis of randomised controlled trials. DATA SOURCES: Embase, Medline, Google Scholar, PubMed and the Cochrane controlled trials register from inception until 3 January 2021. ELIGIBILITY CRITERIA: All randomised trials comparing intubation outcomes between PFT (PFT group) and standard polyvinylchloride (standard polyvinylchloride group) tubes. RESULTS: Analysis of the 13 eligible trials showed no significant difference in successful first-attempt intubation rate [risk ratio (RR) 1.20, 95% confidence interval (CI) 0.99 to 1.44] (6 trials, 568 participants), trauma risk (RR 0.83, 95% CI 0.67 to 1.03) (5 trials, 501 participants) as well as the overall risks of epistaxis (RR 0.58, 95% CI 0.26 to 1.31) (3 trials, 262 participants), sore throat (RR 0.90, 95% CI 0.70 to 1.17) (4 trials, 451 participants) and hoarseness (RR 0.71, 95% CI 0.44 to 1.14) (4 trials, 451 participants) between the two groups. However, the intubation time was slightly shorter (weighted mean difference −4.2 s, 95% CI −7.4 to −1.0 s) (8 trials, 759 participants) and the risks of severe epistaxis (RR 0.15, 95% CI 0.03 to 0.84) (3 trials, 262 participants) and overall difficulty in airway manipulation (RR 0.48, 95% CI 0.29 to 0.80) (8 trials, 647 participants) were lower in the PFT group than those in the standard polyvinylchloride group. Trial sequential analysis conclusively confirmed a shorter intubation time with PFT tubes than with standard polyvinylchloride tubes, whereas other intubation outcomes were inconclusive. CONCLUSION: The use of PFT tubes for airway manipulation was associated with a shorter intubation time compared with the standard polyvinylchloride tubes. The results of trial sequential analysis suggest the need for further trials and meta-analysis to compare other intubation outcomes associated with the two devices. TRIAL REGISTRATION: PROSPERO CRD42020197670. Abstract : Supplemental Digital Content is available in the text